Tripterygium glycosides for safely controlling disease activity in systemic lupus erythematosus: a systematic review with meta-analysis and trial sequential analysis - Chen, Yifan; Wang, Liuding; Li, Nannan; Zhou, Caiyun (Frontiers in Pharmacology, 2023)
Background: Tripterygium glycosides have been used to treat systemic lupus erythematosus (SLE) for a long time, showing the effects of immune regulation. We aimed to evaluate the benefits and risks of Tripterygium Glycosides Tablets (TGT) for patients with SLE. Methods: We searched electronic databases and clinical trial registries for relevant randomized controlled trials (RCTs). We identified eligible RCTs and assessed risk of bias. We conducted a meta-analysis to estimate the pooled effects. The Trial Sequential Analysis (TSA) 0.9.5.10 software was used to verify the reliability of the results. Results: Eight RCTs encompassing 538 patients with SLE were included. TGT combined with conventional treatments (CTs) was superior to CTs alone in reducing lupus activity (MD = −1.66, 95% CI = −2.07 to −1.26, P < 0.00001, low-certainty evidence) and improving overall response rate (ORR) (RR = 1.21, 95% CI = 1.11 to 1.32, P < 0.0001, moderate-certainty evidence). The robustness of the results was confirmed by TSA. Regarding safety, there was no statistical difference in the overall incidence of adverse reactions between the two groups. Conclusion: In patients with SLE, TGT might safely reduce disease activity. However, further high-quality studies are needed to firmly establish the clinical efficacy of TGT.